Renal Function and Ultrasound Imaging in Elderly Subjects. (4th December 2014) - Zanoli, Luca; Romano, Giulia; Romano, Marcello; Rastelli, Stefania; Rapisarda, Francesco; Granata, Antonio; Fatuzzo, Pasquale; Malaguarnera, Mariano; Castellino, Pietro
Abstract : We evaluated in elderly subjects (a) the ability of GFR formulas to discriminate chronic kidney disease (CKD), (b) the correlation between renal morphology and function, and (c) the usefulness of combined r-US and GFR formulas to detect CKD. A total of 72 patients were enrolled (mean age 80 ± 7 years, male sex 44%, serum creatinine 0.98 ± 0.42 mg/dL, and CKD 57%). Cockcroft-Gault showed the highest sensitivity (78%) and specificity (94%) for CKD and was correlated with kidney volume (R = 0.68, P < 0.001 ). All formulas failed to provide a reliable estimate of GFR. In multivariate analysis, Cockcroft-Gault < 52 mL/min and kidney sinus section area < 28 cm 2 showed the highest accuracy for the identification of CKD subjects (AUC 0.90, P < 0.001 ). MDRD and CKD-EPI differed significantly for GFR ≥90 mL/min. Conclusions . Cockcroft-Gault < 52 mL/min was able to discriminate subjects with CKD but all formulas failed to provide a reliable estimate of GFR. The combined use of r-US and Cockcroft-Gault formula improved the ability to discriminate CKD in elderly subjects.